PENGEMBANGAN MODUL AJAR BERBASIS PEMBELAJARAN BERDIFERENSIASI PADA MATERI STATISTIKA TERHADAP GAYA BELAJAR SISWA - Florensia Dasilva Nince; Reni Astuti; Marhadi Saputro (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2023)
This study aims to develop teaching modules based on differentiated learning on statistical material on the learning styles of Grade VIII students at SMP Negeri 1 Belimbing that are valid, practical, and effective. This research is a development research that refers to the model according to Brog and Gall which is modified into 7 steps, namely (1) potentials and problems (2) data collection (3) product design (4) design validation (5) design revision (6) trial product (7) product revision. The instruments used were validation sheets, questionnaires and posttests. Questionnaires are used for expert validation, teacher and student responses, and posttest questions. This study produced teaching modules based on differentiated learning towards student learning styles with a validity level of 81.5% with very valid criteria, teacher and student response questionnaire results with an average of 93.05% with very practical criteria and student posttest results of 75% with effective criteria.